Urgensi Penerbitan Izin Jasa Penilai Properti Sederhana - Irwan, Yudi; Ratna Sediati, Dyah Sulistyani; Sugiyo, Sugiyo (Universitas Semarang, 2022)
The purpose of this research is to investigate the implementation of issuing permits for simple property appraisal services in Indonesia, the challenges in their issuance, and efforts to overcome them. The research method used is normative juridical research with a legislative approach. The urgency of this research lies in examining the implementation of issuing permits for simple property appraisal services in Indonesia. This study will elaborate on the results of the analysis of the implementation of permits for simple property appraisal services in Indonesia, associated with theories and regulations related to the issues under discussion. The results of this research indicate the issuance of permits for simple property appraisal services in Indonesia. It begins with prospective simple property appraisers going through the stages of becoming public appraisers, starting from basic education to the submission of a public appraiser permit. Constraints in the licensing process for simple appraisers often arise in the application submission phase and the applicants' lack of understanding in using the online application elSa-PK. This is due to the insufficient socialization of the application usage process with prospective appraisers.Tujuan penelitian ini adalah untuk mengetahui implementasi penerbitan izin jasa Penilai Properti Sederhana di Indonesia, kendala dalam penerbitannya dan upaya mengatasinya. Metode penelitian yang dipergunakan penelitian yuridis normatif dengan pendekatan perundang-undangan. Urgensi Penelitian ini akan meneliti tentang implementasi penerbitan izin jasa penilai properti sederhana di Indonesia. Penelitian ini akan menguraikan tentang hasil analisis dari implementasi penerbitan izin jasa Penilai Properti Sederhana di Indonesia, yang dikaitkan dengan teori dan peraturan perundang-undangan yang terkait dengan permasalahan yang dibahas. Hasil penelitian ini menunjukkan penerbitan izin jasa Penilai Properti Sederhana di Indonesia. diawali dengan pihak calon Penilai Properti Sederhana wajib melakukan tahapan menjadi Penilai Publik dimulai dari Pendidikan dasar samapi dengan pengajuan izin penilai publik. Kendala dalam proses perizinin penilai sederahana pengajuan aplikasi pengajuan permohonan properti sederhana sering error, dan kurangnya pemahaman para pemohon menggunakan daring Aplikasi elSa-PK. Hal tersebut karena kurangnya sosialisasi cara penggunaan kepada calon penilai.